Single phase multifunctional integrated converter for electric vehicles - Kondreddy Sreekanth Reddy; Sreenivasappa B. Veeranna (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
In this paper, a single phase multifunctional integrated converter is proposed for electric vehicles (EVs) with single stage power conversion. The main objective of the proposed topology is to reduce the weight, size, and cost of the power electronic converter system used in EVs compared to the existing topologies that are already available in the industries. The novelty of the proposed topology includes: (i) single converter for charging, propulsion and regenerative braking; (ii) reduction of number of switches to reduce the switching and conduction losses; (iii) improving the efficiency by reducing the value of inductor; (iv) power factor correction for AC grid; and (v) improving the total harmonic distortion of the grid current. The complete analysis of the various modes of operation of the proposed topology is analyzed and implemented through MATLAB/Simulink software simulation and a power factor of 0.9999 and a current total harmonic distortion (THD) of 2.16% is achieved. The proposed topology is also compared with the existing topologies in terms of number of switches, diodes, inductors and capacitors used.